Prediction of Complex-Valued Signals by Using Complex-Valued LMK Algorithm - Menguc, Engin Cemal; Acır, Nurettin (Ieee, 2017)
In this study, the adaptive prediction of complex valued signals has been realized by using the complex-valued least mean Kurtosis (CLMK) algorithm. The prediction performance of the CLMK algorithm has been evaluated on three benchmark complex-valued signals and a complex-valued real-world radar data by comparing with the traditional least mean square (CLMS) algorithm. Simulation results have verified that the CLMK algorithm outperforms the CLMS algorithm.
25th Signal Processing and Communications Applications Conference (SIU) -- MAY 15-18, 2017 -- Antalya, TURKEY
Keywords: complex-valued adaptive filter; least mean Kurtosis; prediction problem